Financing the provision of global public goods - P. B. Anand (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This paper examines the concept of global public goods (GPGs) and in that context explores the extent of aid (ODA) presently being diverted to GPG provision and whether such diversion skews aid-flows towards some recipients and whether diverting aid to GPG provision crowds out aid for conventional development activities. These are examined on the basis of OECD data for the late 1990s. The main argument of this paper is that ODA should not be used for financing GPG provision by developing countries. Instead, it is suggested that other sources of financing the provision of GPGs should be developed keeping in view the various technologies by which the GPGs can be produced and design principles for supra-national institutions. Various arguments from Sandler, Barrett and Kanbur are considered. In particular, Kanbur's suggestion of two tensions involving the principles of economies of scale, subsidiarity, economies of scope and specialization, is explored further. Some examples of issues where a GPG is produced as a joint product of actions by national governments are considered by looking at data on eight different indicators for 1995. Problems in using the joint product approach to GPG provision are also discussed.
Keywords: H41; F35; D62; O19; H87; 330; global public goods; international organizations; aid; externality; Global Environment Facility; Öffentliches Gut; Entwicklungshilfe; Externer Effekt; Internationale Organisation